ZnI2-catalyzed carbocyclization of arylalkynes leads to the synthesis of polysubstituted dihydro- and tetrahydroquinoline derivatives. Issue 25 (18th June 2020) - Cai, Xiaochen; Pan, Yongjie; Wang, Chaoyang; Qian, Guoying; Rong, Zhouting
Graphical abstract: Highlights: Development of a novel zinc-catalyzed carbocyclization. A cheap and facile access to various dihydro- and tetrahydroquinolines. Formation of up to 3 carbon–carbon bonds in a single step. Abstract: A ZnI2 -catalyzed carbocyclization of arylalkynes has been developed for the construction of various polysubstituted dihydro- and tetrahydroquinoline derivatives. This inexpensive method extends the potential of zinc catalysis to the formation of up to three carbon–carbon bonds and three new rings in a single step with high diastereoselectivity.